Tratamiento de elección de fracturas expuestas de tibia en politraumatizados del área de traumatología del Hospital Teófilo Dávila en el primer semestre del 2012 - Peñaloza Buele, Yasmín C. (2013)
The goal of this in investigation was to make a descriptive study of the treatment of choice of exposed fractures of tibia in polytrauma patients at Teófilo Dávila Hospital on first semester, 2012. This is a descriptive, retrospective and cross study. The data were taken during the months of January to June 2012.